Exploring the socio-psychological drivers of climate adaptation among rural women in Uttarakhand: a TPB framework approach - Simran Pundir; Rabindra N. Padaria; Aiswarya S; Rashmi Singh; Girijesh Singh Mahra; Sitaram Bishnoi; Bhaskar Ghosh; Md. Yeasin; Praveen KV; Shantanu Rakshit; Priti Priyadarshani; Sudip Kumar Gorai; et al. (Frontiers in Sustainable Food Systems)
Women in Uttarakhand are particularly vulnerable to the impacts of climate change due to limited access to resources, land ownership, and decision-making power. These vulnerabilities are further intensified by the region's mountainous landscape, which is highly susceptible to climatic disturbances such as erratic rainfall, temperature fluctuations, and landslides. As key contributors to household welfare and agricultural activities, rural women's adaptive behaviors play a critical role in mitigating climate-related risks and fostering community resilience. This paper investigates climate change ABs among rural women in Uttarakhand, India, within the framework of the Theory of Planned Behavior (TPB). A multistage sampling approach was employed, with purposive selection of two districts—Tehri Garhwal and Rudraprayag—identified as highly vulnerable to climate change. The study examines the relationships between perceived behavioral control (PBC), subjective norms, and attitudes by employing Partial Least Square Structural Equation Modeling (PLS-SEM), exploring their influence on women's intention to adopt adaptation strategies. The findings indicate that PBC, risk perception (RP), and social norms (SN) significantly influence behavioral intention (BI) and adaptation behavior (AB). The analysis revealed that RP and PBC are major predictors of BI to adopt climate adaptation practices, with significant impacts from SN and self-efficacy beliefs. The results emphasize the critical role of social and psychological factors in shaping the climate adaptation decisions of rural women, highlighting the need for gender-sensitive interventions that foster empowerment and access to resources. The study also demonstrates the effectiveness of the TPB framework in understanding rural women's ABs in Uttarakhand and suggests that enhancing women's control over resources and fostering supportive SN can significantly improve their climate resilience. Future research should explore the application of TPB in broader rural contexts, with particular emphasis on empowering women through policy support, education, and community engagement to promote sustainable adaptation strategies in climate-vulnerable regions.